ANALISIS KESULITAN GURU DALAM PENULISAN KARYA TULIS ILMIAH PADA GURU MGMP EKONOMI SMA NEGERI DI KOTA PEKANBARU - Astuti, Nyi; Gimin, Gimin; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTScientific Writing became a way for teachers to develop their profession . For teachers who are able to develop their profession, among other awards given by promotions one of them made of Scientific Writing Classroom Action Research Reports. Difficulties experienced preparing scientific papers by researchers or teachers who did Classroom Action Research (CAR). The difficulties were mainly related to the lack of technical understanding in compiling Scientific Writing. The fewer people who know the essay, the development of scientific ideas is less widespread. The purpose of this study was to determine the difficulties teachers in systematics writing essay on economics teacher state high schools in the city of Pekanbaru. The study population was economics teacher who never made a scientific paper of classroom action research ever conducted and the sample in the study of 20 people. The technique of collecting data using questionnaires, documentation and interviews. Analysis using descriptive analysis method. The study showed economic analysis master difficulty in making scientific writing of 40.6 % experienced considerable difficulty, 34% less experience difficulties, 14.4% had difficulty , not 6.7% and 3.9% have difficulty experiencing very difficult . It can be concluded that in general economics teacher in SMA Pekanbaru enough experience difficulty in writing Essay on Classroom Action Research.Keywords: Scientific Writing, Classroom Action Research, Congress Subject Teacher (CST) Economy In State Senior High School Of Pekanbaru.